KINASE INHIBITOR PROTEIN-1 (Kip-1) SEBAGAI BIOMARKER RISIKO KEGANASAN LEUKOPLAKIA - , Supriatno, Prof. Dr. Hadi Sunartyo, MSc.,Sp.PM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Oral leukoplakia is a precancer lesion which common in developed countries. It has a strong correlation with alcohol and tobacco consumption, and it is often transformed to malignancy. The purpose of the study was to investigate the expression of Kip1 protein in human oral leukoplakia paraffin block toward malignant risk, and to know the relationship between expression of Kip-1 and its clinical characteristic. Non-experimental design with consecutive sampling was performed in the study . All of the oral leukoplakia sample was delivered from Department of Anatomy Pathology, School of Dentistry, Tokushima University, from 1993 to 2003. Medical record and paraffin block record was used to screen the patients clinical characteristic. Samples were stained by Kip-1 protein using immunohistochemistry procedure. Data was analyzed by nonparametric chi-square test and logistic regression test with significant level of 95%. Results of the study revealed that expression of Kip-1 protein was significantly increased in homogenous leukoplakia compared with that of non-homogenous leukoplakia (P=0.001). Same result was detected in correlation between Kip-1 expression with hystological level, smoking habit, and dysplasia (P=0.001). However, expression of Kip-1 protein was not significantly to age (P=0.234) and sex (P=0.101) factors. The other result showed that risk factor of displasia was interfered by smoking habit (P=0.000) and type of leukoplakias (P=0.002). In conclusion, expression of Kip-1 protein may be used as a biomarker of malignant risk of oral leukoplakia. Down-regulation of Kip-1 expresses the poor condition of leukoplakia. Expression of Kip-1 protein has a significant correlation with type of leukoplakia, level of hystology, and smoking habit. Risk factors of dysplasia were influenced by smoking habit and type of leukoplakia.